Співвідношення категорій «форма» та «джерело» права - Чубоха, Н.; Chubokha, N. (Волин. нац. ун-т ім. Лесі Українки, 2018)
Стаття присвячена дослідженню актуальних питань зовнішнього виразу правових норм вітчизняного права, серед яких значне місце займають закони, але суттєво підвищилась роль договірних форм права, в т.ч. міжнародно-правових, відбулося зниження питомої ваги підзаконних актів, що приймаються на виконання законів. Проведено аналіз форм права з метою вивчення можливостей їх удосконалення правотворчості, систематизації законодавства та вияву у ньому прогалин. Розкрито сутність та зміст основних юридичних категорій, які характеризують форми права, визначено особливості їх прояву у приватному праві; досліджено співвідношення понять «форма права» і «джерело права», виділено юридичні ознаки форм права та їх місце і роль у регулюванні приватних відносин. The article is devoted to the study of the topical issues of the external expression of the legal norms in the Ukrainian law. The study has revealed a significant increase of the role of the contractual forms of law, including international legislature, and vice versa, a decrease in the share of the subordinate legislation acts adopted for the purpose of the law enforcement. The analysis of the forms of law provides opportunity to determine their potential for improvement in the law-making process, to systematize the legislature and to reveal the gaps in it. The emphasis is laid on the essence and content of the main legal categories that characterize the forms of law and their peculiar features in the private law. The key findings of the study contribute greatly to better understanding of the correlation between the concepts «form of law» and «source of law». The article provides important information about the legal features of the forms of law and their place and role in regulating private relations. The term «source of law» should be used in the cases when we consider the causes, conditions and other factors that lead to the development of certain rules of behavior and have an impact on the formation of the content of legal norms. The term «form of law» expresses the external expression of the legal norms, giving them the status of legal and general rules of conduct.
Correlation between the Categories «Form» and «Source» of Law
Keywords: форма права; джерело права; природне право; позитивне право; правотворча діяльність; законодавчий процес; form of law; source of law; natural law; positive law; law-making activity; legislative process